Reimagining English Language Instruction: Key Principles for Creative and Sustainable Learning - Gusak, Liudmyla Ye.; Malenitskyi, Denys S. (My University, 2025)
This article presents a set of key principles designed to modernize and personalize English language teaching through creative and learner-centered approaches. While English remains one of the most widely taught subjects in Ukraine, traditional methods continue to dominate classrooms, leading to limited progress in communicative competence. Based on practical teaching experience, field observations, and current pedagogical research, the authors identify four core principles that help reimagine the English learning process: prioritizing speaking over grammar, starting language acquisition at an early age, integrating creative educational technologies, and aligning language learning with personal interests and hobbies. Each principle is supported by empirical insights and classroom practices that emphasize motivation, confidence, and enjoyment as key components of sustainable learning. The first principle addresses the outdated legacy of Soviet education, where English lessons focused almost exclusively on grammar drills. The article argues that fluency should be prioritized over grammatical perfection, and that learners should be encouraged to speak even with mistakes. The second principle highlights the cognitive advantages of early exposure to English, supported by evidence from a practical experiment. The third principle explores a wide range of creative tools, including Artificial English Environments, Virtual Theatre, digital media, and outdoor lessons, to make language learning more dynamic and immersive. The fourth and most comprehensive principle suggests that learners should not force themselves into rigid academic routines, but instead connect their education to personal interests – doing what they love, but in English. The article follows a structured academic format and provides relevant examples from practice. It also discusses the role of modern technologies, such as social media, music, movies, and video games, in making language learning an integral part of everyday life. The proposed approach not only enhances language skills but also encourages autonomy, emotional involvement, and long-term motivation.
Keywords: creative learning; English language teaching; learner-centered approach; speaking fluency; early exposure; Artificial English Environment; Virtual Theatre; personalized learning.; 378.147:811.111